A double blind randomized clinical trial as preemptive and preclosure analgesia using bupivicaine in post operative pain - Kuradagi, Shridhar; Bidinal, Bharathkumar (International Surgery Journal, 2016)
Background: Post-operative pain management has been a constant challenge to many of the surgeons. Effective relief of pain has got physiological and psychological benefits. Because of their side effects most of the analgesic dosage is inadequate. There is need for developing newer modalities which can provide good analgesia with fewer side effects. The aim of the study was to compare preemptive and preclosure infiltration of bupivacaine in reducing post-operative pain and analgesic requirement. Methods: Double blind randomized clinical trial was done in GIMS Hospital Gadag, Karnataka, India. Total of 40 patients, 10 undergoing open cholecystectomy, 10 undergoing laparoscopic cholecystectomy, 20 undergoing elective laparotomy were included in study. Post-operative pain measured using numerical VAS and amount of analgesic use. Results: In the whole group comparison though the pain score was less in preemptive group but it was not significant. Requirement of rescue analgesia occurred early in preclosure group and also there was significant difference in analgesic requirement at 6th hour and at 10th hour. Conclusions: Overall, though preemptive infiltration of bupivacaine reduces pain better than preclosure infiltration in common abdominal surgeries but it may be not significant. Preemptive infiltration of bupivacaine delays the time duration for the requirement of first analgesic dose and may also be helpful in reducing the number of analgesic doses in postoperative period when compared to preclosure infiltration in common abdominal surgeries.